The epidemiology of knee injuries in English professional Rugby Union - Dallalana, R. J.; Brooks, J. H. M.; Kemp, S. P. T.; Williams, A. W. (The American Journal of Sports Medicine, 2007)
Background: Detailed injury epidemiology is an invaluable tool for reducing risks associated with sporting injuries. Very little accurate injury surveillance data exist regarding knee injuries in professional rugby.